2011
DOI: 10.1186/1755-8166-4-28
|View full text |Cite
|
Sign up to set email alerts
|

Isolated trisomy 7q21.2-31.31 resulting from a complex familial rearrangement involving chromosomes 7, 9 and 10

Abstract: BackgroundGenotype-phenotype correlations for chromosomal imbalances are often limited by overlapping effects of partial trisomy and monosomy resulting from unbalanced translocations and by poor resolution of banding analysis for breakpoint designation. Here we report the clinical features of isolated partial trisomy 7q21.2 to 7q31.31 without overlapping phenotypic effects of partial monosomy in an 8 years old girl. The breakpoints of the unbalanced rearranged chromosome 7 could be defined precisely by array-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Chromosomal rearrangements detected in routine banding cytogenetics currently can be characterized easily by fluorescence in situ hybridization (FISH) and/or array-comparative genomic hybridization (aCGH) (Manolakos et al 2010;Weimer et al 2011). Obviously, aCGH provides higher resolutions; however, FISH still has several advantages over the array-based approaches (Tsuchiya et al 2008;Manolakos et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal rearrangements detected in routine banding cytogenetics currently can be characterized easily by fluorescence in situ hybridization (FISH) and/or array-comparative genomic hybridization (aCGH) (Manolakos et al 2010;Weimer et al 2011). Obviously, aCGH provides higher resolutions; however, FISH still has several advantages over the array-based approaches (Tsuchiya et al 2008;Manolakos et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We extended our study examining clinical data of pure distal versus pure interstitial 7q duplication comparing the six cases reported in the literature with those observed in the present child ( Table 2 ). 3 6 10 17 20 22 Analyzing these results, it appears evident that minor nonspecific craniofacial features, intellectual delay, and skeletal impairment with minor frequency were the most representative clinical signs presented both in the group of children with distal and in the present child with interstitial chromosome 7q involvement.…”
Section: Discussionmentioning
confidence: 63%
“…8 Pavone et al reported a female child with pre-and postnatal growth retardation and complex malformations with microcephaly, lack of cortical thickening, hypoplastic inferior vermis in association with signs of CS as partial sacral agenesis and complete coccygeal agenesis, preintrasacral dermoid, intradural lipoma, ectopic anus, and tethered cord. [19][20][21][22] The child showed a de novo duplication of 7q34-q35 and an 8.8-Mb deletion on 7q36. This sequence includes HLXB9 (CS) gene which in the case report of Pavone et al was not found.…”
Section: Distal 7qmentioning
confidence: 99%
“…A detailed characterization of chromosomal rearrangements detected in routine banding cytogenetics can nowadays be done easily by fluorescence in situ hybridization (FISH) and/or array-comparative genomic hybridization (aCGH) (Manolakos et al 2010; Weimer et al 2011). While in aCGH, a higher resolution may be achieved, FISH still has several advantages over the array-based approaches (Manolakos et al 2010).…”
mentioning
confidence: 99%